Meningkatkan Keaktifan Belajar Anak dalam Kegiatan Temu Minggu Menerapkan Metode BCM (Bermain, Cerita, Menyanyi) - Yustina Patrisia Bona; Nikolaus Anggal; Yohanes Yuda (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2017)
This paper describes the result of a Classroom Action Research (CAR) done by the Writer with the purpose to know the activeness and activities of the missioner children at Santo Matius Church-station, Muara Siram Makmur, in attending the children Sunday meeting session, using the PSTS (Playing, Story Telling, and Singing) method. The subjects are 20 missioner children of primary school ages, at Santo Matius Church-station, Muara Siram Makmur. The study was conducted in 3 action cycles, using 3 different teaching materials: 1) Jesus’ presence brings new spirit for action cycle I; 2) Jesus the good shepherd for action cycle II; and 3) becoming jesus’ disciples for action cycle III. The results of the study showed that the children’ activeness in attending the children sunday meeting session had increased. This fact could be seen from the decrease of the percentage of the children obtaining the activeness score belonging to the activeness score category of less active, and the increase of the percentage of the children obtaining the activeness score belonging to the activeness score categories of sufficiently active, active and very active. The activities of the children who attended the Sunday meeting session also increased, by the increase of the average score of every activity indicator at action cycle II and action cycle III, if compared to the average score of every activity indicator at action cycle I.